Enhanced immunogenicity of a positively supercharged archaeon thioredoxin scaffold as a cell-penetrating antigen carrier for peptide vaccines - Cavazzini, Davide; Spagnoli, Gloria; Mariz, Filipe Colaco; Reggiani, Filippo; Maggi, Stefano; Franceschi, Valentina; Donofrio, Gaetano; Müller, Martin; Bolchi, Angelo; Ottonello, Simone (Frontiers in Immunology, 2022)
Polycationic resurfaced proteins hold great promise as cell-penetrating bioreagents but their use as carriers for the intracellular delivery of peptide immuno-epitopes has not thus far been explored. Here, we report on the construction and functional characterization of a positively supercharged derivative of Pyrococcus furiosus thioredoxin (PfTrx), a thermally hyperstable protein we have previously validated as a peptide epitope display and immunogenicity enhancing scaffold. Genetic conversion of 13 selected amino acids to lysine residues conferred to PfTrx a net charge of +21 (starting from the -1 charge of the wild-type protein), along with the ability to bind nucleic acids. In its unfused form, +21 PfTrx was readily internalized by HeLa cells and displayed a predominantly cytosolic localization. A different intracellular distribution was observed for a +21 PfTrx-eGFP fusion protein, which although still capable of cell penetration was predominantly localized within endosomes. A mixed cytosolic/endosomal partitioning was observed for a +21 PfTrx derivative harboring three tandemly repeated copies of a previously validated HPV16-L2 (aa 20-38) B-cell epitope grafted to the display site of thioredoxin. Compared to its wild-type counterpart, the positively supercharged antigen induced a faster immune response and displayed an overall superior immunogenicity, including a substantial degree of self-adjuvancy. Altogether, the present data point to +21 PfTrx as a promising novel carrier for intracellular antigen delivery and the construction of potentiated recombinant subunit vaccines.